2010
DOI: 10.1111/j.1537-2995.2010.02905.x
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected suppression of anti‐Fya and prevention of hemolytic disease of the fetus and newborn after administration of Rh immune globulin

Abstract: This case demonstrates the potential immunosuppressive properties of RhIG for down regulation of a possible clinically significant alloantibody, not anti-D, where no D+ antigen is in the circulation of the mother. The case illustrates the potential utility for using RhIG to modulate antibody levels in situations other than for classical suppression of anti-D production. Although the mechanism in this case is unknown, TGFβ-1-mediated or antibody-mediated immunosuppression to soluble nonparticulate antigens are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…As stated above, the working mechanism of RhIG has not been elucidated yet. There is also clear evidence for an immunomodulatory activity of RhIG, demonstrated by immunosuppression of anti‐Fya antibody responses in pregnancy in D– women and increased levels of immunomodulatory cytokines like transforming growth factor‐β and prostaglandin E2 after RhIG administration . It might be speculated that glycosylation level of RhIG, of which the fucosylation is the most striking feature, also affects these immunomodulatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…As stated above, the working mechanism of RhIG has not been elucidated yet. There is also clear evidence for an immunomodulatory activity of RhIG, demonstrated by immunosuppression of anti‐Fya antibody responses in pregnancy in D– women and increased levels of immunomodulatory cytokines like transforming growth factor‐β and prostaglandin E2 after RhIG administration . It might be speculated that glycosylation level of RhIG, of which the fucosylation is the most striking feature, also affects these immunomodulatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…Her anti-Fy a titer was observed to decrease dramatically following the administration of multiple doses of prophylactic antenatal RhIG. 29 …”
Section: Discussionmentioning
confidence: 99%
“…One published case report additionally suggests a possible non‐D‐specific suppressive effect of RhIG. Branch and colleagues reported a case of a pregnant woman with a high‐titer anti‐Fy a . Her anti‐Fy a titer was observed to decrease dramatically after the administration of multiple doses of prophylactic antenatal RhIG.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, it was reported that the YB2/0 form of a mAb-D, T125, had greater interactions with both FcγRIIIa and FcγRIIb than the CHO form, thus indicating that low fucosylated anti-D would be effective in this mechanism of B cell suppression 82 as well as in rapid RBC clearance 29 . (e) Other "non-specific" immunomodulatory effects of prophylactic anti-D could be caused by the anti-D or many other alloantibodies in the donor pool of immuno-globulins (similar to IVIG) using these mechanisms, such as reductions of anti-Fy a in a case report 83 and of anti-HLA sensitisation in a large survey 84 . HLA class I antigens (Bg) are expressed on most cells including RBC of some normal donors 85 .…”
Section: Summary Of Clearancementioning
confidence: 99%